Optimalisasi Pemanfaatan Platform Pembelajaran untuk Meningkatkan Pengelolaan Kelas yang Baik Dimasa Pandemi - Fatimah, Siti (Prosiding University Research Colloquium, 2021)
This study aims to see the extent of the use of learning platforms and the impact of using various learning platforms. The research method used a survey method with the subject being the teacher of SD Negeri Purwosari, Secang District. Based on the results of the study, the use of the learning platform is still not optimal and causes several obstacles during online learning. These obstacles come from both teachers, parents and students. Teachers who lack innovation and only use the Whatsapp and Youtube platforms, students who have difficulty understanding the material, teachers who have difficulty evaluating or assessing learning, and parents who complain a lot about online learning. Based on the research results, optimizing the use of online learning platforms is able to improve good classroom management during the pandemic.